Financial fragility in open-ended mutual funds: The role of liquidity management tools - Peter G. Dunne; Lorenz Emter; Falko Fecht; Raffaele Giuliana; Oana Peia (Deutsche Bundesbank, 2024)
We study the role of liquidity management tools (LMTs) in mitigating financial fragility in investment funds during the COVID-19 market distress. We employ a unique dataset that reports the availability of different types of LMTs in a sample of Irish-domiciled corporate bond funds. We find that funds with access to price-based tools such as redemption fees or anti-dilution levies experienced lower net outflows in March 2020, as compared to funds with only quantity-based tools such as redemption gates, temporary suspensions, or redemptions in kind. This difference is stronger among funds with a high sensitivity of flows to past performance and reflects both higher gross inflows and lower gross outflows during this episode. Funds with price-based LMTs also rebalance their portfolios towards less liquid bonds. This portfolio rebalancing results in a lower price decline of bonds held disproportionally more by funds with price-based LMTs in our sample of Irish-domiciled funds.
Keywords: G2; G23; 330; liquidity management tools; investment funds; COVID-19; financial fragility